2016
DOI: 10.1002/jbm.a.35744
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SDF‐1α on low dose BMP‐2 mediated bone regeneration by release from heparinized mineralized collagen type I matrix scaffolds in a murine critical size bone defect model

Abstract: The treatment of critical size bone defects represents a challenge. The growth factor bone morphogenetic protein 2 (BMP-2) is clinically established but has potentially adverse effects when used at high doses. The aim of this study was to evaluate if stromal derived factor-1 alpha (SDF-1α) and BMP-2 released from heparinized mineralized collagen type I matrix (MCM) scaffolds have a cumulative effect on bone regeneration. MCM scaffolds were functionalized with heparin, loaded with BMP-2 and/or SDF-1α and implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
(75 reference statements)
0
32
0
1
Order By: Relevance
“…However, these supraphysiological BMP‐2 doses are associated with several potential adverse effects—ectopic bone formation in particular. The modification of heparinized MCM scaffolds has been shown to attenuate the initial burst of BMP‐2 and to facilitate a long‐term release for up to 6 weeks . This effect allows the reduction of the applied BMP‐2 concentration, which could prevent concentration‐related side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these supraphysiological BMP‐2 doses are associated with several potential adverse effects—ectopic bone formation in particular. The modification of heparinized MCM scaffolds has been shown to attenuate the initial burst of BMP‐2 and to facilitate a long‐term release for up to 6 weeks . This effect allows the reduction of the applied BMP‐2 concentration, which could prevent concentration‐related side effects.…”
Section: Discussionmentioning
confidence: 99%
“…These drawbacks can be attenuated by a retarded BMP‐2 release from the biomaterial, which has been the focus of recent studies by our group. The modification of MCM with the glycosaminoglycan heparin can prevent the initial burst of growth factors with heparin‐binding domains and enable a sustained release over weeks in vitro ; a sustained release of BMP‐2 over 6 weeks has been verified in vitro . Besides the retarding effect on the growth factor release, heparin modification has also been shown to significantly promote the proliferation and osteogenic differentiation of mesenchymal stroma cells in vitro .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the low cost, easy availability, and status of heparin as an already FDA- and EMA-approved product, has meant that researchers are harnessing its properties, preferentially over that of other GAGs (such as HS) to improve growth factor delivery [188,189,192,194,440]. Gaining particular prominence is the use of heparin-loaded delivery vehicles for skeletal TE, where biomaterials decorated with heparin have been extensively studied both in vitro and in vivo, for their ability to reduce the dosing requirements and improve the therapeutic potential of BMPs, such as BMP2 [188,189,194,455,456,457,458,459,460]. Most of these studies have shown very promising results, with heparin-loaded biomaterials improving BMP2 delivery, release, and osteogenic potential.…”
Section: The Problems Associated With Heparinmentioning
confidence: 99%
“…The vessels were identified by lumen-like structures filled by erythrocytes (33). Tissue specimens were then fixed in 10% formaldehyde, dehydrated in graded alcohol solutions of 50, 70, 90, 96, and 100%, cleared in xylene (Merck, Darmstadt, Germany), and embedded in paraffin (Merck).…”
Section: Skin Evaluation and Tissue Samplingmentioning
confidence: 99%